Influenza Vaccination Is Associated With Reduced Cardiovascular Mortality in Adults With Diabetes: A Nationwide Cohort Study - Daniel Modin; Brian Claggett; Lars Køber; Morten Schou; Jens‐Ulrik Stæhr Jensen; Scott D. Solomon; Orly Vardeny; Filip K. Knop; Susanne Dam Nielsen; Michael Fralick; Christian Torp‐Pedersen; Gunnar Gislason; et al. (2020)
OBJECTIVE: Recent influenza infection is associated with an increased risk of atherothrombotic events, including acute myocardial infarction (AMI) and stroke. Little is known about the association between influenza vaccination and cardiovascular outcomes in patients with diabetes. RESEARCH DESIGN AND METHODS: We used nationwide register data to identify patients with diabetes in Denmark during nine consecutive influenza seasons in the period 2007-2016. Diabetes was defined as use of glucose-lowering medication. Patients who were not 18-100 years old or had ischemic heart disease, heart failure, chronic obstructive lung disease, cancer, or cerebrovascular disease were excluded. Patient exposure to influenza vaccination was assessed before each influenza season. We considered the outcomes of death from all causes, death from cardiovascular causes, and death from AMI or stroke. For each season, patients were monitored from December 1 until April 1 the next year. RESULTS: A total of 241,551 patients were monitored for a median of four seasons (interquartile range two to eight seasons) for a total follow-up of 425,318 person-years. The vaccine coverage during study seasons ranged from 24% to 36%. During follow-up, 8,207 patients died of all causes (3.4%), 4,127 patients died of cardiovascular causes (1.7%), and 1,439 patients died of AMI/stroke (0.6%). After adjustment for confounders, vaccination was significantly associated with reduced risks of all-cause death (hazard ratio [HR] 0.83, P < 0.001), cardiovascular death (HR 0.84, P < 0.001), and death from AMI or stroke (HR 0.85, P = 0.028) and a reduced risk of being admitted to hospital with acute complications associated with diabetes (diabetic ketoacidosis, hypoglycemia, or coma) (HR 0.89, P = 0.006). CONCLUSIONS: In patients with diabetes, influenza vaccination was associated with a reduced risk of all-cause death, cardiovascular death, and death from AMI or stroke. Influenza vaccination may improve outcome in patients with diabetes.